2020
DOI: 10.1371/journal.pone.0216914
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of antimicrobial resistance determinants of Escherichia coli isolates obtained from meat in South Africa

Abstract: This study aimed to characterise antibiotics resistance of Escherichia coli isolates from the formal meat sector (FMS) and informal meat sectors (INMS). MethodA total of 162 and 102 E. coli isolates from the FMS, and INMS respectively were isolated by standard culture-based, and biochemical reactions. The isolates were further confirmed by polymerase chain reaction (PCR). The disc diffusion method was used to screen for antimicrobial susceptibility against 19 different antibiotics. The presence of class 1-2 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…Prolonged illness, disability, and death occur when microorganisms do not respond to standard treatment (Jindal et al, 2015;WHO, 2018). Studies from sub-Saharan Africa have reported high AMR (Alabi et al, 2013;Jaja et al, 2020;Llor and Bjerrum, 2014). Routine AMR monitoring in small cohort studies such as these is equally important to understand the actual burden of AMR in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged illness, disability, and death occur when microorganisms do not respond to standard treatment (Jindal et al, 2015;WHO, 2018). Studies from sub-Saharan Africa have reported high AMR (Alabi et al, 2013;Jaja et al, 2020;Llor and Bjerrum, 2014). Routine AMR monitoring in small cohort studies such as these is equally important to understand the actual burden of AMR in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with the findings of the studies conducted in Iran, United States, Saudi Arabia, and China, which reported an increasing development of AR against tetracycline of 66.9%, 63%, 90.71%, and 43%, respectively by Salmonella isolates [ 22 , 23 , 24 , 25 ]. In South Africa, over 70% of the antibiotics used in livestock production are available over the counter [ 26 ], and this contributes to the increased prevalence of AR in the country. Tetracyclines have been an important class of antibiotics in the health and production of food animals for decades, as they are used in veterinary medicine for illness prevention and control [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey conducted by Eagar et al [ 33 ], 16.7% and 12.4% of tetracyclines and sulphonamides were commonly used antibiotics in animals in South Africa between the years 2002 and 2004. The Stock Remedies Act of 1947 in South Africa consents tetracycline to be purchased over the counter without a prescription from a veterinarian [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 E. coli isolates (92.31%) isolated from se'i meat samples showed resistance to two or more Kallau et al (2018) showed 57.3% prevalence of MDR E. coli isolates with 39 resistance patterns. Jaja et al (2020) reported a total of 20 MDR patterns with 3-10 antibiotic classes of E. coli isolates. Antibiotic-resistant E. coli in animal products can seriously threat public health (Rahman et al, 2017).…”
Section: Percentage Of Multidrug Resistant (Mdr) E Coli Isolated From Se'i Meatmentioning
confidence: 99%